Queen's Park Hotel, Port of Spain; Largest and Leading Hotel in Trinidad, B.W.I. - (:unkn) unknown (Ace Studio, Trinidad, 2010)
This postcard shows a front view of the Queen's Park Hotel which is located on the southern side of the Queen's Park Savannah. In this view we see the 1937, five storey, Art Deco renovation at the centre of the building and there are several taxis parked on the road opposite the hotel. Postcard number 7.
Colour: Sepia; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Savannas--Trinidad and Tobago; Historic buildings--Trinidad and Tobago; [1945]; Historic hotels--Trinidad and Tobago; Hotels--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Port of Spain; Trees--Trinidad and Tobago; Architecture--Trinidad and Tobago; Hospitality industry--Trinidad and Tobago; Fences--Trinidad and Tobago; Automobiles--Trinidad and Tobago; Transportation--Trinidad and Tobago; Taxicab industry--Trinidad and Tobago; Taxicabs--Trinidad and Tobago; Queen's Park Savannah (Port of Spain)